2009
DOI: 10.1530/rep-08-0298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HSPA8, an evolutionarily conserved oviductal protein, on boar and bull spermatozoa

Abstract: Previous studies have shown that a soluble protein fraction derived from preparations of apical plasma membrane (APM) of the oviductal epithelium enhances the in vitro survival of mammalian spermatozoa. Here, we show that the survival enhancing property of the soluble protein fraction seems to depend significantly upon heat shock 70 kDa protein 8 (HSPA8 previously known as HSPA10). The following findings in the present study enabled us to draw this conclusion: first, using proteomic analysis, we identified a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 38 publications
8
87
0
1
Order By: Relevance
“…One member of this family, HSPA8, secreted by the oviduct, was shown to support the viability of spermatozoa in the boar, the ram, and the bull (46,51). The increase of abundance of HSPA8 we found in the oviduct fluid at estrus may be linked to a role in sperm survival around ovulation.…”
Section: Discussionmentioning
confidence: 64%
“…One member of this family, HSPA8, secreted by the oviduct, was shown to support the viability of spermatozoa in the boar, the ram, and the bull (46,51). The increase of abundance of HSPA8 we found in the oviduct fluid at estrus may be linked to a role in sperm survival around ovulation.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that HSPA8 exerts protective effects on spermatozoa, enhancing sperm survival at body temperature in vitro in boars, rams, and bulls [7][8][9][10]. The objective of the present study was to extend these studies and investigate the possibility that the protective effects of HSPA8 might be exploited for the improvement of bovine sperm cryopreservation protocols.…”
Section: Discussionmentioning
confidence: 95%
“…Although it often functions at the intracellular level, it has also been detected in the extracellular space, where it exerts protective effects on cell viability, apparently possessing both proapoptotic and antiapoptotic properties depending on the situation [3,4]. Within the context of sperm biology, recent studies have shown that HSPA8 is produced by oviductal epithelial cells during sperm transport [5,6] and enhances boar, ram, and bull sperm survival [7][8][9][10] in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…These are potentially important findings, as the oviduct and oviductal sperm storage play key roles in reproduction by providing a secure reservoir in which spermatozoa can attain full fertilising properties. Hsc70 appears to interact with components of the sperm cell surface membrane (117,118) and exposure to Hsc70 prolongs the survival of boar, bull and ram sperm (117,120). Studies have now shown that a recombinant form of Hsc70 (HSPA8) rapidly promotes the viability of uncapacitated spermatozoa, the ability of spermatozoa to bind to oviductal epithelial cells, enhances the performance of in vitro fertilisation procedures, and decreases sperm mitochondrial activity (121).…”
Section: Extracellular Cell Stress Proteins In Cancermentioning
confidence: 99%